Z-pinning techniques to improve energy absorption capabilities of CFRP tubular structures - Ramírez, J. G.; Ghasemnejad, Hessam (Springer, 2023)
This paper investigates the use of z-pinning reinforcement in CFRP tubular structures under axial impact, to find the optimum design to increase the specific energy absorption (SEA). Through-the-thickness reinforcement is known as a technique to improve integrity and fracture resistance in composite materials and structures. Manufacturing and testing of unpinned tubular structures are conducted to create a base model to validate numerical results. A finite element model of the tube under dynamic impact is developed using LS-DYNA software, conducting parametric studies, mesh sensitivity analysis and trigger modelling research. The proposed z-pinning modelling techniques are researched, and an energy-based contact model is proposed to model pinned areas. Five different designs of reinforced tubes are designed and analysed, to find the optimum z-pinned pattern in terms of SEA. The novelties of this research indicate that z-pinning can improve the SEA and reduce the initial collapse load during crushing. Our results indicate that the vertical banded design shows the highest SEA and least initial collapse load values in comparison with the unpinned specimen, which indicates an improvement in the crashworthiness parameters of z-pinned composite tubes.
Keywords: z-pinning; composites; absorbed energy; impact; delamination; fracture